How do Lebanese patients perceive the ideal doctor based on the CanMEDS competency framework? - Mabel Aoun (BMC Medical Education, 2019)
Abstract Background During their training, Lebanese medical students develop a high medical expertise but are not focusing on other competencies such as communication, collaboration, erudition, professionalism, leadership and health promotion. There is also insufficient data about patients’ preference for these skills. This study describes the different weights patients attribute to these physician’s competencies. Methods This is a cross-sectional study based on a questionnaire distributed to 133 Lebanese patients. It included 15 questions assessing how patients prioritize the physician’s competencies, with open-ended questions asking them to define “the good doctor”. Krippendorff’s alpha coefficient was used to analyze the reliability of the competencies’ classification. Results One hundred twenty five patients completed the questionnaire in this cross-sectional study. Their mean age was 48 ± 16.76 years. When classifying competencies, 73.6% opted for medical expertise as first choice and 48% put communication as second. Based on the Krippendorff’s coefficient, we identified a moderate agreement for the seven choices (alpha = 0.44). In open-ended questions, patients defined the good doctor in 325 answers: 64.3% mentioned medical expertise, 34.1% high ethics and 26.2% communication. Conclusions This patient-centered study concurs well with the worldwide practice that puts medical expertise at the center of medical education. However Lebanese patients don’t perceive equally other competencies and favor professionalism and communication that should be integrated in priority in students’ curricula.